2017
DOI: 10.1152/ajprenal.00179.2016
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of T-cell activation by the CTLA4-Fc Abatacept is sufficient to ameliorate proteinuric kidney disease

Abstract: Diabetic nephropathy (DN) remains an unmet medical challenge as its prevalence is projected to continue to increase and specific medicines for treatment remain undeveloped. Activation of the immune system, in particular T-cells, is emerging as a possible mechanism underlying DN disease progression in humans and animal models. We hypothesized that inhibition of T-cell activation will ameliorate DN. Interaction of B7-1 (CD80) on the surface of antigen presenting cells with its binding partners, CTLA4 (CD152) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 47 publications
1
25
0
Order By: Relevance
“…Increased renal T-cell recruitment were detected both in patients with DN and diabetic mice 31. A series of investigations inhibiting T-cell activation or targeting Th17 ameliorated diabetic renal damage in animal models 32–35. In our study, we found the T-cell immune response was suppressed in C3aR −/− diabetic mice compared with WT diabetic mice by microarray, indicating a link between C3a and T-cell adaptive immunity in DN.…”
Section: Discussionsupporting
confidence: 49%
“…Increased renal T-cell recruitment were detected both in patients with DN and diabetic mice 31. A series of investigations inhibiting T-cell activation or targeting Th17 ameliorated diabetic renal damage in animal models 32–35. In our study, we found the T-cell immune response was suppressed in C3aR −/− diabetic mice compared with WT diabetic mice by microarray, indicating a link between C3a and T-cell adaptive immunity in DN.…”
Section: Discussionsupporting
confidence: 49%
“…In the same line, induction of DN in mice without T and B lymphocytes (Rag1-/-mice) showed that lymphocytes activate glomerular macrophages, induce podocyte injury, and increase albuminuria [59]. Pharmacological inhibition of T-cell activation with CTLA4-Fc abatacept also reduced albuminuria in mice with DN [60].…”
Section: T Lymphocytesmentioning
confidence: 94%
“…Importantly, infiltration of immune cells is a key feature of DN [17]. Activated T cells (CD4+ and CD8+) are mainly located in the renal interstitium of diabetic kidneys [44][45][46]. Although CD4+ IL-17+ cells are the main source of IL-17A production, other cells, including macrophages, neutrophils, natural killer, dendritic, and mast cells, have also been described to produce this cytokine.…”
Section: Il-17 In Human Diabetic Nephropathymentioning
confidence: 99%